2012
DOI: 10.2478/v10101-012-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Health awareness, motor performance and physical activity of female university students

Abstract: Health awareness, motor performance and physical activity of female university students Study aim: To assess body composition, health awareness and cardiorespiratory fitness in female university students differing in volume of obligatory physical activity classes. Material and methods: 109 female students of the University of West Hungary volunteered to participate in the study. The subjects were divided into two groups according to frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
2
8
0
1
Order By: Relevance
“…Anthropometric data in the sample of S2 show greater height, weight, BMI values and greater body fat percentages in both males and females than the study fifteen years ago (S1). We did not measure muscle mass, but recently in an other study in Hungary, Konczos and collegues [24] demonstrated that the muscle mass of the studied non-PE college students is under the physiologically optimal level. They found correlation between higher muscle mass and active lifestyle, and also between lower muscle mass and lower aerobic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropometric data in the sample of S2 show greater height, weight, BMI values and greater body fat percentages in both males and females than the study fifteen years ago (S1). We did not measure muscle mass, but recently in an other study in Hungary, Konczos and collegues [24] demonstrated that the muscle mass of the studied non-PE college students is under the physiologically optimal level. They found correlation between higher muscle mass and active lifestyle, and also between lower muscle mass and lower aerobic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The number of PE sessions in HEI have decreased in the last few years as well [25]. On the other hand, alcohol drinking and smoking among students continuously increase during college and university years paralleled with irregular eating habits [2,24]. A longitudinal study in the USA between 1996-2008 showed that PA and maximal oxygen uptake of university students were reduced along with an increase of bodyfat percentages [33].…”
Section: Introductionmentioning
confidence: 99%
“…Anthropometric parameters as body height, body mass and body mass index have been used for epidemiologic health studies of population as a convenient and inexpensive measurement of overweight and obesity [1,2,11,13]. Anthropo metric indicators show the physical development of humans from childhood to adulthood [3,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The anthropometric parameters of the individual also affect qualitative and quantitative physical activity [8,18], which is closely related to physical fitness [9,20], and also forms an integral part of each person's daily life [10,12,16]. Physical fitness also has morphological and functional properties which allow an individual to be able to be engaged in physical activities [11][12][13]. The anthropometric parameters depend on environmental and household conditions, internal and external risk factors that are able to induce imbalance in human health status [14,15,16,23,24,27].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Grappasoni et al [6] evaluated health risks awareness of seafarers while the studies of Grappasoni et al [7], Chowdhury et al [8] and Laraquie et al [9] studied on the STI/HIV/AIDS which is considered to be a significant infectious disease for seafarers. There are also various studies examining the health awareness of undergraduate students in many different fields [10][11][12][13][14][15][16]. All these studies on seafarers and students indicate that education and information about health issues should be given regularly.…”
Section: Introductionmentioning
confidence: 99%